Pengaruh Terapi Akupunktur Pada Titik BL 13, LI 11, SP10, ST36 Dan HT7 Terhadap Perbaikan IG.E Pasien Pruritus Dermatitis Pada Santri Pondok Pesantren Di Surakarta - Sumanto Sumanto; Maria Dewi Christiyowati (Poltekkes Kemenkes Surakarta, 2017)
Abstract : Dermatitis Atopic, Ig.E, Pruritus, Santri/ Students Ponpes Surakarta. The purpose of this study to determine the influencing of acupuncture therapy with poin Bl 13, Li 11, SP 10, ST 36 and HT 7 to improve Immunoglobin E (Ig.E) and to reduce pruritus scale for Santri with dermatitis in Pondok pesantren of Surakarta. Quasi experiment with one group pre test – post test design. The focus of research is the use of acupuncture to improve Ig.E and to reduce pruritus scale in Dermatitis Atopic. Acupuncture therapy acupuncture performed by trained therapists who have a permit or license from the competent authority official. Data were collected by interview/ anamnesis, observation and fill out a questionnaire after getting acupuncture therapy. Data analysis will use the t-test and ANOVA One-way to justify the data pre and post acupuncture treatment, then processed with SPSS 16.0 series. Acupuncture is effective in improving Ig.E and reducing pruritus intensity for santri/student in Pondok Pesantren Al Kahfi of Surakarta.